Gender Differences in the Effect of Facial Attractiveness on Perception of Time - Tian, Yu; Li, Lingjing; Yin, Huazhan; Huang, Xiting (Frontiers in Psychology, 2019)
Time perception plays a fundamental role in human social activities, and it can be influenced in social situations by various factors, including facial attractiveness. However, in the eyes of observers of different genders, the attractiveness of a face varies. The current study aimed to explore whether gender modulates the effect of facial attractiveness on time perception. To account for individual differences in esthetic standards, the critical stimuli presented to each participant were selected from an image pool based on the participant’s own attractiveness judgments. In Experiment 1, men and women performed a stimuli selection task followed by a temporal reproduction task to measure their time perception of faces of different attractiveness levels and gender. To control for the potential influence of task order, Experiment 2 flipped the order of the selection and temporal tasks. Taken together, the experiments showed that both men and women exhibited longer reproduced durations for attractive opposite-sex faces than for unattractive opposite-sex faces; conversely, in the same-sex face condition, women still exhibited longer reproduced durations for attractive faces than for unattractive faces, whereas the effect of facial attractiveness on time perception among men tended to be smaller or even fail to reach significance. These results suggest that gender differences play an important role in the effect of facial attractiveness on time perception.